Characterization of the Bahia Blanca estuary by data analysis and numerical modelling. - Campuzano, Francisco Javier (2014)
The Bahía Blanca Estuary is a complex system of channels and tidal flats where the most important deep water harbour system of Argentina is located. The main goal of the present work was to obtain a hydrodynamic conceptual model for the Bahía Blanca coastal area. For this reason, a combined analysis of observed data and numerical modelling has been performed for the whole area. The gained knowledge on the system hydrodynamics could aid in the decision support for navigation security, waste water discharges management, sediment dredging and rejection operations among other applications. Due to the Bahia Blanca coastal vast area, hydrodynamic observations are scarce and located near the populated areas. In order to describe the hydrodynamics of such a complex and large system, the analysed tidal and current data from different periods have been completed through numerical modelling. Data analysis served to determine the main processes governing the Bahia Blanca hydrodynamics, to characterise the area using general descriptors, to provide inputs for the numerical model and aid to evaluate its performance. In addition, a 2-Dimensional application was set up using the MOHID water modelling system for the Bahía Blanca estuary. This application aimed to gain a better understanding of the system dynamics, to explain and test the consistency of the observed data and to reproduce the processes taking place. Model results were in good agreement with the analysed data and served to confirm an inconsistency found on the sea level observations. The combination of both methodologies served to further describe the hydrodynamic processes governing this coastal area and also to obtain a conceptual model for the water and properties circulation in the Bahía Blanca estuary.